Are bioplastics the solution to the plastic pollution problem? - Sandra Pascoe Ortiz (PLoS Biology, 2023)
We live our lives immersed in plastic pollution: a problem that is becoming more acute. Viable alternatives that can reduce plastic pollution are being sought. Could bioplastics be the hoped-for solution to this problem?